A Peculiar Case of Allergic Granulomatous Reaction to Red Pigment: A Tattoo Touch-Up Treated Surgically - Antonella Tammaro; Ganiyat Adenike Ralitsa Adebanjo; Francesca Magri; Camilla Chello; Chiara Iacovino; Francesca Romana Parisella; Alessandro Capalbo; Fabiola Luzi; Gabriella De Marco (Allergies, 2021)
This case report describes a 50-year-old woman who developed an allergic granulomatous reaction after a tattoo touch-up.